Sustained effect of remaining cementite on the corrosion behavior of ferrite-pearlite steel under the simulated bottom plate environment of cargo oil tank. (September 2016) - Hao, Xuehui; Dong, Junhua; Etim, Ini-Ibehe Nabuk; Wei, Jie; Ke, Wei
Highlights: Cementite accumulates continuously on steel surface during the immersion test. Residual cementite continuously promotes the steel corrosion by galvanic effect. A corrosion evolution model of ferrite-pearlite steel is proposed. The anodic dissolution occurs on the ferrite phase as a charge transfer step. Cathodic reaction of HER on remaining cementite is a diffusion-control process. Abstract: This investigation aims to study the sustained effect of remaining cementite on the corrosion of ferrite-pearlite steel in an acidic chloride solution (i.e. simulated bottom plate environment of cargo oil tank). The results show that the corrosion rate of ferrite-pearlite steel was continuously accelerated with extending the immersion time, caused by the continuously enhanced galvanic effect between the remaining lamellar cementite and exposed ferrite phases. Electrochemical impedance spectroscopy (EIS) data further indicated that the promoted dissolution of ferrite phases was controlled by charge transfer process. Meanwhile, the hydrogen evolution reaction occurred on cementite was controlled by the diffusion process.